Evagrius Ponticus' Rejection of a Magical Understanding of Grace - Vazquez, Santiago Hernán (2023)
In recent years, a growing number of studies have presented - in one way or another - various psychotherapeutic projections of a set of spiritual practices of early Christian monasticism. In an attempt to establish a dialogue between the doctrines of Late Antiquity and contemporary psychotherapy, it could be risky to extrapolate anachronistic terms, questions and discussions that are foreign to the original context of the Early Church Fathers. In order to overcome this difficulty, we will try to elucidate Evagrius Ponticus' model of psychospiritual integration through his particular understanding of the effective relations between grace and nature. This will possibly allow us to translate and understand the current interest in his psycho-spiritual model in the same terms as those in which it was formulated by Evagrius. In his effort to think about how the process of complete healing of man takes place, Evagrius takes up intuitions and ideas from the Hippocratic and Platonic traditions. These traditions disapprove of magic as an act of impiety towards the divine order inscribed in the {greek word presented}. Evagrius follows this fundamental intuition of rejection of magic and sorcery to integrate it into a new Christian synthesis that strives to move away from a magical understanding of the action of grace. Now, as Evagrius moves away from a magical conception of grace, certain theoretical-practical knowledge related to mental and spiritual health can be found in his writings. Evagrius is particularly interested in specifying how grace operates in the cognitive-emotional dynamics that intervene in the healing processes of the soul without contradicting or magically suspending the immanent laws of the {greek word presented}.